Implementasi Forward Chaining pada Sistem Pakar Diagnosa Kerusakan Laptop Berbasis Web: Studi Kasus Layanan Servis Laptop - Dimas Permadi; Dwipa Handayani; Prio Kustanto; Muhammad Yasir; Achmad Noeman; Agus Hidayat (Journal of Informatic and Information Security, 2025)
Laptop damage diagnosis at PT Tsurtech Solution is currently carried out manually, which can take more time and requires the technician's experience to identify problems accurately. This research aims to design and implement a web-based expert system to assist in diagnosing laptop damage based on symptoms inputted by users. The system is developed using the Forward Chaining algorithm, a data-driven reasoning method that matches facts (symptoms) with a set of predefined rules to conclude the type of damage. The system is built using the Waterfall development method, assisted by UML diagrams, and implemented with PHP programming language and MySQL database. Blackbox Testing is used to evaluate the system’s functionality. The results show that the system can be used as a supporting tool to help both users and technicians perform initial laptop damage diagnosis more quickly and efficiently.